Research on Grid Structure of Backbone Power Transmission Network - Su, Yunche; Shen, Li; Li, Ao; Rong, Jun; Wang, Yunling; Cheng, Siqi (2023 6th International Conference on Energy, Electrical and Power Engineering (CEEPE), 2023)
The scale of generation supply and power grid continues to expand, the grid structure is subject to the double constraints of short-circuit current and network stability, which is supposed neither be too tight nor too loose. How to find a balance point among them has become the key to power transmission network planning. In response to the above problem, three types of grid construction modes is proposed in this paper. The advantages and applicable scenarios of each modes in terms of power flow distribution, short-circuit current control effect, long-term development adaptability, and operational flexibility is analyzed. The feasibility of the proposed method are verified by a case study of a practical provincial power grid.